Implementasi Manajemen Risiko berdasarkan PBI No. 13/23/PBI/2011 Studi: Produk Ijarah Multijasa pada PT. BPRS ADAM kota Bengkulu - Yuliza, Meli; Hak, Nurul; Yustati, Herlina (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2021)
The purpose of this study was to determine how the application of  risk management in Ijarah Multijasa products at PT. BPRS ADAM. The research method used is a qualitative method with data collection techniques through interviews with 8 respondents and direct observation to PT BPRS Adam. Then the data is described, analyzed  and discussed to answer the problems posed. From the results of this study it was found that the application of risk management based on PBI No. 13/23 / PBI / 2011 on Ijarah Multijasa products at PT. BPRS Adam is in line.